(untitled) (Journal of Nobel Medical College, 2023)
Background: Dyslipidemia is a common issue among diabetic patients and is associated with an increased risk of cardiovascular disease. Non-High Density Lipoprotein-cholesterol has emerged as a valuable marker for assessing combined cardiovascular risk in diabetes. Measures to improve the Non-High Density Lipoprotein-cholesterol within optimal level might improve the glycemic status and decrease the cardiovascular risk. This study aims to examine the relationship between Non-High Density Lipoprotein-cholesterol and glycated hemoglobin levels in type 2 diabetic patients. Materials and Methods: A hospital-based comparative cross-sectional study was conducted on 544 individuals diagnosed with type 2 diabetes. The classification of lipid profile and glycemic control was carried out as per the National Cholesterol Education Program Adult Treatment Plan III and American Diabetes Association guidelines. Results: Our study found that Non-High Density Lipoprotein-cholesterol levels was higher in uncontrolled diabetes (157.9±46.8) compared to controlled diabetes (132.6±40.6), with a statistically significant difference (P<0.001). There was a weak positive correlation between Non-High Density Lipoprotein-cholesterol and glycated hemoglobin levels (r=0.37).Among the total participants, 226 (41.5%) had optimal Non-High Density Lipoprotein-cholesterol level whereas 318 (58.5%) had high Non-High Density Lipoprotein-cholesterol. Conclusion: This study confirms a positive correlation between Non-High Density Lipoprotein-cholesterol and HbA1c levels in type 2 diabetic patients. Dyslipidemia prevalence was substantial, emphasizing the importance of achieving target Non-High Density Lipoprotein-cholesterol levels for improved glycemic control and cardiovascular risk reduction.